Estrategias de producción cinematográfica alternativa en el cantón Latacunga. - Moscoso Almache, William Xavier (2018)
The present work describes an innovative proposal to alternative cinema in the canton Latacunga doing so relevant and educational. Allows you to know which strategies are structured by the collective cinematographic and other audiovisual works of the canton Latacunga. For that reason, it was possible to interpret their origin, organization, strategies, and how do they generate audiovisual products with their own resources, giving to understand and interpret their results compared to consumers of the internet and its target audience. is focused on the community, directly benefiting the collective film of the canton Latacunga. Thanks to the different methods applied was obtained different variables that allowed to determine what are the ways to generate alternative cinema and audiovisual production. A measurement of your target audience (Young People Latacunguenos) through surveys, which allowed to know his perspective on the collective agreements. Among the results showed that the young people consider favorably the generation of collective dedicated to alternative cinema, however agreed that it is a product that does not consume it. Finally proposes lines of research after they have investigated it has been verified that in the province of Cotopaxi there are no studies that mention or involve alternative film collective, proposing to generate debate, as well as the emergence of new organizations dedicated to film production.